DEXSim: an experimental environment for distributed execution of replicated simulators using a concept of single simulation multiple scenarios. (April 2014) - Choi, Changbeom; Seo, Kyung-Min; Kim, Tag Gon
This paper presents an efficient and scalable experimental environment for distributed execution of replicated simulators. By taking a performance-centered approach, the proposed technique makes the best use of distributed hardware resources for faster data collection. Accordingly, the primary contribution of this work is to describe how the environment improves scalability and utilizes distributed hardware resources efficiently. To do this, we suggest a new concept of single simulation multiple scenarios and propose a distributed execution simulation framework regarding the following three aspects: (1) layered architecture model design; (2) protocol definitions interacting with them; and (3) framework implementation. The proposed model architecture and protocol definitions guarantee a straightforward structural scalability and an efficient load-balanced utilization between hardware resources. Moreover, the framework operates simulation execution automatically without users' extra work. In order to prove the efficiency of the proposed framework, we performed three extensive experiments with different models, that is, different systems. The experimental results show that simulation performance increases proportionally with the number of hardware resources, minimizing the overhead of the proposed framework's utilization.